Vitsentzos Kornaros, Erotokritos : A Translation with Introduction and Notes - Betts, Gavin (Byzantina Australiensia Ser, 2004)
Intro -- Vitsentzos Kornaros, Erotokritos -- Copyright -- Dedication -- Contents -- List of illustrations from the 1710 manuscript -- Preface -- Introduction -- The Cretan Renaissance -- The author -- The poem -- Summary -- Themes -- Literary antecedents -- The world of Erotokritos -- Manuscripts, editions and reception -- Material from the first edition (1713) -- Title page -- Dedication to Georgios Tsandiris -- The printer to those who will read the present book -- The characters who speak in the poem -- Map -- Translation -- Part A -- Part B -- Part C -- Part D -- Part E -- Endnotes -- Bibliography -- Index.